Social Rehabilitation as Legal Policy Protection for Women Victims of Terrorist Cyber Indoctrination - Budiono, Arief; Absori, Absori; Mohammad, Genta Arya; Sugeng, Esmara; Yuspin, Wardah; Zuhdi, Syaifuddin; Rizka, Rizka (Faculty of Law, Universitas Pekalongan, 2024)
Introduction: It is noted that 513 women with Indonesian citizenship traveled to Iraq and Syria after being impacted by cyber indoctrination. Among these women, there are those with a manus minustra (victim) status. Some are trapped in Iraq and Syria overseas as they were brought there by their families when they were still young or were babies. Methods: This research employed the classical dogmatic juridical method with a literary approach. This research was conducted to find the best solution for women as victims of terrorists’ indoctrination who have not committed terror acts or women who migrated to Iraq and Syria when they were still young or were babies. Results and Discussion: Social rehabilitation is only given to indoctrination victims who have not committed terror, as well as women who were trapped in Iraq and Syria because they were brought over by their families when they were still young/babies, thus requiring identification. Social rehabilitation is crucial to prevent equal punishments between victims and offenders. Some countries apply social rehabilitation with various methods and requirements, such as Uzbekistan, Germany, and the United States. Conclusion: Rehabilitation is possible as the providing institutions are experienced in giving social rehabilitation to children of terrorism perpetrators. Social rehabilitation in these three countries was successful with various degrees of success. It is deemed as more successful than punishments as the former prevents victims from obtaining further indoctrination in jails